Assessment of Nursery Technology in the Tropics - a Composite Index of Healthy and Plantable Seedlings - Bahuguna, V. K. (Indian Forester, 1996)
This paper highlights the impact of nursery operations like sowing method, density of seed, use of shade and mulch etc. on the production of healthy and plantable seedling in the tropics. An attempt has been made to propose an alternative formula for analysing and ranking the results of nursery experiments in the form of a composite index of healthy and plantable seedlings.